A Simplified Environmental Assessment Methodology for Research Projects as an Alternative to Life-Cycle Assessment. (December 2019) - Fulton, Matt; Nurse, Alex; Plater, Andy
Small and medium enterprises and research institutes engaged on eco-innovative research projects are often required to account for environmental benefits of new products, processes, or services. This article describes an environmental assessment methodology for calculating auditable environmental benefits, highlighting case studies as examples. It addresses the challenges involved in conducting assessments of products that have yet to be commercialized by taking into account the quality and confidence of the data and enabling nonexperts to engage with the process to a well-informed level. The method draws on the most pertinent and accessible information to develop a reliable overview of the reportable outputs while minimizing the resource and expertise required by measuring only the change in circumstance. The process is flexible enough to cater to projects from a range of sectors, with different expertise levels, but in-depth enough to be considered an acceptable quantification of environmental outputs by rigid external reporting requirements.